Sejarah wilayah perbatasan Entikong-Malaysia, 1845-2009 satu ruang dua tuan - Wulandari, Triana; Djaenuderadjat, Endjat (Gramata, 2009)
History of Indonesia-Malaysia border region in Entikong, Kalimantan Barat Province; collection of articles.